Manganese Deficiency is Associated with Histological Changes in Date Palm Fronds Showing Brittle Leaf Disease Symptoms - Abassi, R.; Namsi, A.; Bennasri, M.; Ben Abdalah, H.; Ben Maachia, S.; Ouerghi, Z.; Durán-Vila, Núria (2017)
Several diseases, pests and physiological disorders threat date palm life. Among them, Brittle leaf disease or, in French, Maladie des feuilles cassantes (MFC) is a lethal disease that has acquired alarming proportions since the 1960s, when it was first observed in southern Tunisia. Up to now no causal agent has been found. Previous studies have reported that brittle fronds are deficient in manganese but the mechanisms involved in symptom expression have not yet been identified. In this study, an anatomical investigation was carried out in order to identify the deleterious effect of MFC on the development and structure of palm fronds. Results showed that in old healthy fronds the major tissue is schlerenchyma, which is characterized by very thick lignified cell walls and is often associated with conducting tissue. Indeed, large vessels are surrounded by schlerenchyma fibers that are strongly lignified when compared with those of young fronds. Diseased young fronds have almost the same shape as the healthy young fronds. Nevertheless, in old diseased fronds MFC induces important structural changes. Xylem and phloem vessels are larger, taking more space through the fibers that are smaller in number and size, and tighter. The larger diameter of the lumen and the lower thickness of the fibers present in the fronds in advanced disease stages, decreases the lignin content of cells walls, leading to an increased frond friability, which gives "the brittle leaf disease" its name.